Improving the Quality of Personal Health Care with Community Nursing Interventions for School-Age Children During the Covid-19 Pandemic - Muflih; Sang Ayu Made Adyani; Endang Nurul Syafitri (proceedinginternational, 2023)
The COVID-19 pandemic is a vulnerable time for the health of school-age children. There is an ineffectiveness of personal health care due to restrictions on mobility and limited access to health care facilities. Therefore, nursing interventions are needed based on a community nursing approach that is appropriate to the problem. The purpose of this study was to determine the effectiveness of community nursing interventions on improving the quality of health care in the aggregate of school-age children during the COVID-19 pandemic. The research method used is action research. The research process is carried out online. The research stage begins with observing the data using the google form application. Nursing intervention design provided through google meet application. Evaluation of the results of its implementation uses indicators of knowledge and obedient behavior. The participants involved were 16 children aged 10-14 years in the Special Region of Yogyakarta, Indonesia. The results of the study showed that the knowledge outcome increased from the level of limited knowledge to high knowledge, the outcome of obedient behavior towards the recommended activities increased from the level of rarely showing to the level of often showing. The conclusion of the study was that community nursing interventions were effective in improving the quality of personal health care with community nursing interventions. So, Nurses in community services can optimize online-based nursing interventions for school-age children during the COVID-19 pandemic.